2015
DOI: 10.1093/infdis/jiv532
|View full text |Cite
|
Sign up to set email alerts
|

Stability of a Vesicular Stomatitis Virus–Vectored Ebola Vaccine

Abstract: The live attenuated vesicular stomatitis virus-vectored Ebola vaccine rVSV-ZEBOV is currently undergoing clinical trials in West Africa. The vaccine is to be stored at -70°C or less. Since maintaining the cold chain is challenging in rural areas, the rVSV-ZEBOV vaccine's short-term and long-term stability at different temperatures was examined. Different dilutions were tested since the optimal vaccine dosage had not yet been determined at the start of this experiment. The results demonstrate that the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 12 publications
0
15
0
Order By: Relevance
“…61 To date, stability data remain scarce, yet one study found that the vaccine stayed stable with comparable viral titers for 7 days when stored at +4°C. 62 In a guinea-pig challenge model, vaccination with VSV-EBOV conferred protection from disease even when stored in various suboptimal conditions over 7 days (4°C, room temperature, 32°C, or three cycles of freeze-thawing from −80°C to room temperature), and only the vaccine kept at 32°C showed a significant reduction in virus titer. 63 The data indicate that short-term interruptions of the cold chain may be tolerated without affecting vaccine efficacy.…”
Section: Stability Of the Vaccinementioning
confidence: 96%
“…61 To date, stability data remain scarce, yet one study found that the vaccine stayed stable with comparable viral titers for 7 days when stored at +4°C. 62 In a guinea-pig challenge model, vaccination with VSV-EBOV conferred protection from disease even when stored in various suboptimal conditions over 7 days (4°C, room temperature, 32°C, or three cycles of freeze-thawing from −80°C to room temperature), and only the vaccine kept at 32°C showed a significant reduction in virus titer. 63 The data indicate that short-term interruptions of the cold chain may be tolerated without affecting vaccine efficacy.…”
Section: Stability Of the Vaccinementioning
confidence: 96%
“…Most viral vectored vaccines are stable for >5 years at −70°C, and a 2–8°C cold chain is required for distribution and storage of adenoviral vectors. One study assessing the recently deployed rVSV-ZEBOV vaccine observed a significant loss of viral titres at a temperature of 4°C after 2 weeks, 39 whereas adenoviral vectors were shown to be stable for 20 days at room temperature in a sucrose buffer. 40 In addition, sensitivity of any VSV-based vaccine to pH changes is presumably dependent on the specific envelope glycoprotein (i.e.…”
Section: Progression Of the Vectored Vaccine Approach: Success Of Rapmentioning
confidence: 99%
“…However, recent in vitro studies demonstrated that a recombinant VSV‐vectored EBOV vaccine was stable for 1 week at 4°C and 24 hr at 25°C. Vaccine titres significantly decreased by 1–2 logs within 12 hr at 40°C, which may pose a limitation in areas with warmer climates, such as Africa (Arnemo et al, ). However, the longevity of VSV‐vectored vaccines baited in blister packs at increasing temperatures has yet to be determined.…”
Section: Other Vaccine Platforms To Consider For Bait‐style Vaccinatimentioning
confidence: 99%